1995
DOI: 10.1111/j.1834-7819.1995.tb03120.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the effects of Nd:YAG and Ho:YAG laser irradiation on dentine and enamel

Abstract: This preliminary study was undertaken to investigate the effects of Nd:YAG and Ho:YAG lasers on enamel and dentine of extracted teeth. The Ho:YAG laser (spot size 250 microns, energy density 4160 J/cm2) produced a cleaner puncture in dentine with less melting of the surrounding tissue than did the Nd:YAG laser (spot size 20 microns), energy density 50,000 J/cm2), which produced considerable melting and recrystallization of dentine and was more difficult to control. It was possible to cut enamel and dentine wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 18 publications
1
17
0
Order By: Relevance
“…This thermal mechanism on explosive vaporization of interstitial water has been proposed for Ho:YAG lithotripsy [29]. However, it is well known that clinical long-pulse Ho:YAG laser ablation of calcified tissue occurs without significant thermal damage to surrounding tissue, i.e., thermal confinement occurs [36]. In addition, holmium lithotripsy creates sharply demarcated craters, with microscopic preservation of crystalline lamella on the crater surface, implying a regular, consistent, and stereotypical lasercalculus interaction [9].…”
Section: Discussionmentioning
confidence: 98%
“…This thermal mechanism on explosive vaporization of interstitial water has been proposed for Ho:YAG lithotripsy [29]. However, it is well known that clinical long-pulse Ho:YAG laser ablation of calcified tissue occurs without significant thermal damage to surrounding tissue, i.e., thermal confinement occurs [36]. In addition, holmium lithotripsy creates sharply demarcated craters, with microscopic preservation of crystalline lamella on the crater surface, implying a regular, consistent, and stereotypical lasercalculus interaction [9].…”
Section: Discussionmentioning
confidence: 98%
“…The effects on the morphology of the surface can range from no apparent surface alteration to rather dramatic melting, resolidification, and evaporation of the enamel. In particular, the Nd:YAG laser produces shallow craters with numerous microcavities, micropores, and microfissures as reported by Hess [13] and others [14][15][16][17]22,24]. These studies, however, only reported changes that occurred morphologically at the surface.…”
Section: Introductionmentioning
confidence: 64%
“…Lasers have been studied for use in the detection [9,25,26] and removal of enamel caries [5,6,28] and cavity preparation [22,29,30,32,34], treating pits and fissures [10,16], in etching the surface for the bonding of dental resin [11,13,20,21,23,24], and in altering the calcium hydroxyapatite crystalline structure to increase caries resistance [7,15]. The types of lasers used in these studies have included: ruby [1,2], carbon dioxide [3][4][5][6][7][8][9][10][11][12]27], Nd:YAG [12][13][14][15][16][17][18][19][20][21][22][23], CO 2 -Nd:YAG [12,23], argon-ion [24]…”
Section: Introductionmentioning
confidence: 99%
“…The laser causes surface melting, followed by recrystallization, resulting in small scattered areas and some opened dentinal tubules. 32,33 The recrystallization of the dentinal apatite and formation of additional stages of calcium phosphate increase resistance of hard tissues to acid demineralization, which reduces dentin permeability. 34,35 The 37% phosphoric acid as well as the acid monomer MDP may not have had the same capacity to demineralize the dentin irradiated with the laser in comparison with the groups in which the laser was not applied.…”
mentioning
confidence: 99%